Construction and Demolition Waste Management: A Systematic Scoping Review of Risks to Occupational and Public Health - Cook, Ed; Velis, Costas A.; Black, Leon (Frontiers in Sustainability, 2022)
Despite the relatively benign characteristics of construction and demolition waste, its mismanagement can result in considerable harm to human health for 200 million workers and those who live and work in proximity to construction and demolition activities. The high number of workers classified as informal, results in a large unregulated and vulnerable workforce at a high risk of exposure to hazards. We focused a systematic scoping review (PRISMA-ScR) on evidence associating construction and demolition waste with hazards and risks in low- and middle-income countries. We reviewed more than 3,000 publications, narrowed to 49 key sources. Hazard-pathway-receptor scenarios/combinations were formulated, enabling indicative ranking and comparison of the relative harm caused to different groups. Though the evidential basis is sparse, there is a strong indication that the combustible fraction of construction and demolition waste is disposed of by open burning in many low- and middle-income countries, including increasing quantities of high chloride-content PVC; risking exposure to dioxins and related compounds. A long-standing and well-known hazard, asbestos, continues to represent a health threat throughout the world, claiming 250,000 lives per annum despite being banned in most countries. In the coming decades, it is anticipated that more than half of all deaths from asbestos will take place in India, where it is still sold. Comparatively, the highest risks from construction and demolition waste exist in low- and middle-income countries where attention to risk mitigation and control is needed. The preprint of this paper is available at https://doi.org/10.31224/osf.io/5tpbz (Cook and Velis, 2020)